2009
DOI: 10.1002/ppap.200931201
|View full text |Cite
|
Sign up to set email alerts
|

Cathode Current Density Distributions in High Power Impulse and Direct Current Magnetron Sputtering Modes

Abstract: During the operation of high power impulse magnetron sputtering discharges, peak currents in excess of 1 000 A may be observed, leading to large instantaneous power levels. To investigate this method of operation, a series of planar probes have been constructed that allow for the spatial and temporal variations of current across the surface of a cathode to be assessed. These measurements provide information on the flux of charged particles to and from the cathode whilst it is being sputtered. Under operating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
3
3
0
Order By: Relevance
“…16 Indeed, Liebig et al 203 have shown using 2D OES that the sputter distribution of the target is wider for an HiPIMS discharge than for dcMS. Similar findings have been reported by Clarke et al 204 This is consistent with empirical observations that show that the width of the ion current density distribution in the target vicinity and thus the erosion width increases with increased target current and voltage, 57 both of which are significantly higher for HiPIMS than for dcMS.…”
Section: Deposition Ratesupporting
confidence: 82%
“…16 Indeed, Liebig et al 203 have shown using 2D OES that the sputter distribution of the target is wider for an HiPIMS discharge than for dcMS. Similar findings have been reported by Clarke et al 204 This is consistent with empirical observations that show that the width of the ion current density distribution in the target vicinity and thus the erosion width increases with increased target current and voltage, 57 both of which are significantly higher for HiPIMS than for dcMS.…”
Section: Deposition Ratesupporting
confidence: 82%
“…where L (= 10 mm) is an assumed mean radial width of the spokes (as used in [12]). The assumption of a Gaussian radial profile fits well observations from previous studies [57]. In the case of the strip probe current density J p (), which is obtained from I p over the narrow strip from the magnetron centre to the outer edge, we ensure that the integral of the constructed function J p (θ, r) over the entire cathode gives the measured discharge current, namely:…”
Section: Inspection Of I P and I Isat Insupporting
confidence: 66%
“…17,18 Here, n i (t) is assumed to be the total ion density in the plasma at any time t during the impulse, β is the percentage of ions attracted back to the target, and γ is the average secondary electrons emission coefficient of the target. The discharge current I (t) at time t is given by…”
mentioning
confidence: 99%